AB0916 Clinical Outcome in A Norwegian Cohort of Patients with Chronic Recurrent Multifocal Osteomyelitis. (10th June 2014) - Lilleby, V.; Johnsson, A.; Knudsen, P.K.; Flatø, B.
Abstract : Background: Chronic multifocal recurrent osteomyelitis (CRMO) is a rare autoimmune, inflammatory disorder that primarily affects children. The disease is characterised by non-infectious, recurrent osteomyelitis, which can be severe and disabling if left untreated. The diagnosis is often made delayed, patients are treated unnecessarily with antibiotics and there is a paucity of information on outcome and disease course. Objectives: The aim of this study was to assess clinical presentation and outcome in a Norwegian Cohort of patients with CRMO. Methods: Retrospective chart review was performed in the 26 patients with CRMO registered at the hospital between 2002 and 2013. Data collected were: age, symptoms at presentation, diagnostics and imaging, delay of diagnosis, number of affected skeletal sites, history and effect of medication, state of disease at latest visit: active disease, clinical partial or full remission (defined as minimum 6 months of continious inactive disease). Patients with minor symptoms, but otherwise inactive disease were categorised as having partial remission. Results: Mean age at disease-onset was 10.5 years (range 5.4-14.0 years), 77% were female, and all patients were Caucasians (26 patients). The mean delay in diagnosis was 1.5 year (range 0.08 - 4.3) and 39% were initially treated with antibiotics. Disease onset was multifocal in 73% and symmetrical manifestations were seen in 25%. Mean disease duration was 4.0 years (range 0.3 -11.3 years). During disease course 85% developed multifocal disease. The most commonly affected skeletal regions were the fibula (65%), followed by the tibia (50%), the femur (42%), the pelvis (35%) and the clavicula (26%). A biopsy was taken in 70%. NSAIDs were given in most patients (89%), resulting in partial (54%) or total (23%) remission in those treated. Methotrexate and corticosteroids were infrequently used (respectively in 8% and 10%). None of the patients were treated with biologics or bisphosphonates. At the latest follow-up 20% still had active disease, 50% were in partial remission and 30% were in total remission, but only 22% were off all medication. Conclusions: We conclude that after a mean disease duration of 4.0 years the majority of patients (80%) obtained a state of remission (partial or total remission), but only a minority (22%) of off all medication. Persistently active disease was seen in 20% of the patients. Methotrexate and corticosteroids were infrequently used and none of our patients were treated with biologics or bisphosphonates. The results may suggest a relative benign disease course in this Norwegian cohort, although few patients reached remission off medication. References: Ferguson PJ and Sandu M. Current understanding of the pathogenesis and management of chronic recurrent multifocal osteomyelitis. Curr Rheumatol Rep 2012: 130 -141 Hedrich et al. Autoinflammtory bone disorders with special focus on chronic recurrent multifocal osteomyelitis. Pediatric Rheumatology 2013, 11:47 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3215